1997
DOI: 10.1128/aem.63.9.3394-3398.1997
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fecal populations of bifidobacteria and lactobacilli and investigation of the immunological responses of their human hosts to the predominant strains

Abstract: The bifidobacterial and lactobacillus populations of fecal samples collected from 10 human subjects were studied. The numbers of bifidobacteria were similar in the fecal samples of all of the subjects, but lactobacillus numbers varied, even between samples collected from the same individual. Analysis of the composition of the bacterial populations by ribotyping and pulsed-field gel electrophoresis to differentiate between strains showed that, at least for the numerically predominant strains, each subject harbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
2
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(99 citation statements)
references
References 13 publications
4
91
2
2
Order By: Relevance
“…The numerically predominant species of bacteria are obligately anaerobic and are represented by both gram-positive and gram-negative genera (Tannock, 1994). It is estimated that more than 400 species of bacteria reside in the human gut, while only 30-40 species represent 99% of the microbiota found in any one human subject (Kimura et al, 1997). At birth, the newborn infant intestine is sterile, but is colonized rapidly thereafter by microorganisms from the mother and the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerically predominant species of bacteria are obligately anaerobic and are represented by both gram-positive and gram-negative genera (Tannock, 1994). It is estimated that more than 400 species of bacteria reside in the human gut, while only 30-40 species represent 99% of the microbiota found in any one human subject (Kimura et al, 1997). At birth, the newborn infant intestine is sterile, but is colonized rapidly thereafter by microorganisms from the mother and the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…In human faeces, lactobacilli generally account for less than 1% of the bacterial community and it has been reported that they were not detected in faecal samples collected from c. 27% of Americans (Finegold et al, 1983;Sghir et al, 2000). Particular Lactobacillus species are reported to be persistent in the intestinal tracts of some humans, undetectable in others or exhibiting temporal changes in strain composition (McCartney et al, 1996;Kimura et al, 1997). Lactobacillus acidophilus, Lactobacillus salivarius, Lactobacilli casei, Lactobacillus plantarum, Lactobacillus fermentum, Lactobacillus reuterii and Lactobacillus brevis are the most commonly isolated species from the human intestine (Mitsuoka, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These facts, along with the size of the gene, make it a good evolutionary clock. 24 Though the 16S rRNA gene is a well-conserved universal marker, however, there are some shortcomings associated with its use. First, the 16S rRNA genes are so well conserved that it results in a limited resolving power.…”
Section: Sequencing Analysis Of Ribosomal Dna and Other Chronometermentioning
confidence: 99%
“…Indeed, excellent subspecies differentiation has been shown using PFGE for a number of organisms, including lactobacilli and bifidobacteria. 24,33 In some cases PFGE has enabled the grouping of bacterial strains within a species, and there are various examples to assess the potential of this technique to characterize bacterial isolates as well. Further, the usefulness of PFGE has been adequately demonstrated in monitoring the changes in the predominant bifidobacterial and lactobacilli populations of human origin, both in individuals over time as well as between individuals.…”
Section: Pulse Field Gel Electrophoresis (Pfge)mentioning
confidence: 99%
See 1 more Smart Citation